Training characteristics of male and female professional road cyclists: A 4-year retrospective analysis - van Erp, T.; Sanders, D.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To describe the training intensity and load characteristics of professional cyclists using a 4-year retrospective analysis. Particularly, this study aimed to describe the differences in training characteristics between men and women professional cyclists. Method: For 4 consecutive years, training data were collected from 20 male and 10 female professional cyclists. From those training sessions, heart rate, rating of perceived exertion, and power output (PO) were analyzed. Training intensity distribution as time spent in different heart rate and PO zones was quantified. Training load was calculated using different metrics such as Training Stress Score, training impulse, and session rating of perceived exertion. Standardized effect size is reported as Cohen`s d. Results: Small to large higher values were observed for distance, duration, kilojoules spent, and (relative) mean PO in men`s training (d=0.44-1.98). Furthermore, men spent more time in low-intensity zones (ie, zones 1 and 2) compared with women. Trivial differences in training load (ie, Training Stress Score and training impulse) were observed between men`s and women`s training (d=0.07-0.12). However, load values expressed per kilometer were moderately (d=0.67-0.76) higher in women compared with men`s training. Conclusions: Substantial differences in training characteristics exist between male and female professional cyclists. Particularly, it seems that female professional cyclists compensate their lower training volume, with a higher training intensity, in comparison with male professional cyclists.